2012
DOI: 10.1099/vir.0.037739-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel reassortant canine H3N1 influenza virus between pandemic H1N1 and canine H3N2 influenza viruses in Korea

Abstract: During recent canine influenza surveillance in South Korea, a novel H3N1 canine influenza virus (CIV) that is a putative reassortant between pandemic H1N1 2009 and H3N2 CIVs was isolated. Genetic analysis of eight genes of the influenza virus revealed that the novel H3N1 isolate presented high similarities (99.1–99.9 %) to pandemic influenza H1N1, except for in the haemagglutinin (HA) gene. The HA gene nucleotide sequence of the novel CIV H3N1 was similar (99.6 %) to that of CIV H3N2 isolated in Korea and Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 18 publications
3
107
0
Order By: Relevance
“…Suppurative pneumonia in combination with neutrophil infiltration and extensive erosion have also been reported (Yoon, et al, 2005;Songserm et al, 2006a;Songserm et al, 2006b;Payungporn et al, 2008;Song et al, 2011). It is worth noting that IAV H3N1 and Pandemic H1N1 subtypes causes mild symptoms in dogs and cats (Lin et al, 2012;Sponseller et al, 2010;Song et al, 2012).…”
Section: B Pathologymentioning
confidence: 78%
See 3 more Smart Citations
“…Suppurative pneumonia in combination with neutrophil infiltration and extensive erosion have also been reported (Yoon, et al, 2005;Songserm et al, 2006a;Songserm et al, 2006b;Payungporn et al, 2008;Song et al, 2011). It is worth noting that IAV H3N1 and Pandemic H1N1 subtypes causes mild symptoms in dogs and cats (Lin et al, 2012;Sponseller et al, 2010;Song et al, 2012).…”
Section: B Pathologymentioning
confidence: 78%
“…Further studies indicated that HA gene originated from CIV H3N2 while the other 7 genes originated from pandemic H1N1. Experimental infection of dog showed low virus shedding with mild pathogenicity compared to CIV H3N2 (Song et al, 2012).…”
Section: Canine Influenza Virus H3n1 (Reassortant)mentioning
confidence: 96%
See 2 more Smart Citations
“…It is likely that such reassortment event between avian and human influenza viruses could have happened many times over, either in humans or in animals (Medina et al 2011). Recently, a new subtype H3N1 was identified as a result of reassortment in the canine genes of human H1N1pdm09 and canine H3N2 influenza viruses highlighting that companion animals may be a critical determinant to act as intermediate hosts for influenza viruses (Song et al, 2012). The influenza A subtype H3N1 is endemic in pigs and it has been seen that several H3N1 containing A(H1N1)pdm09-like segments could pose a threat to public health (Pascua et al, 2013).…”
Section: Introductionmentioning
confidence: 99%